2008
DOI: 10.1063/1.3001605
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium diffusion and trapping in hydrothermally grown single crystalline ZnO

Abstract: Articles you may be interested inEffect of implanted species on thermal evolution of ion-induced defects in ZnO Photoluminescence, morphology, and structure of hydrothermal ZnO implanted at room temperature with 60 keV Sn+ ions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…9 For sample A-1, an average lifetime τ ave of 187 ps is recorded, consistent with that typically found for as-grown (Li-rich) HT ZnO. 16 However, for sample A-3 (Li rich, hydrogenated) τ ave is reduced to 176-177 ps, similar to that for sample B-1 (Li poor, not hydrogenated), while for sample B-3 τ ave is even further reduced to 171 ps, close to the bulk value of ∼170 ps (τ B ) for ZnO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 For sample A-1, an average lifetime τ ave of 187 ps is recorded, consistent with that typically found for as-grown (Li-rich) HT ZnO. 16 However, for sample A-3 (Li rich, hydrogenated) τ ave is reduced to 176-177 ps, similar to that for sample B-1 (Li poor, not hydrogenated), while for sample B-3 τ ave is even further reduced to 171 ps, close to the bulk value of ∼170 ps (τ B ) for ZnO.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 H is a relatively fast diffuser exhibiting an activation energy in the range of 0.8-0.9 eV. 8,9 Less is known about Li diffusion. However, an early study by Lander 10 suggests an activation energy of 1 eV for migration of Li i .…”
Section: Introductionmentioning
confidence: 99%
“…8,20,27 Typically, the activation energy of the deuterium motion is found to be somewhat higher than that of hydrogen, which results from the difference in the zero-point energy of the O-H and O-D species. We found that in the case of V Zn H 2 , thermal equilibrium between V Zn H 2 and V Zn H * 2 is reached already at room temperature, which complicates the process of generating a stable nonequilibrium distribution between the ground and metastable states of V Zn H 2 .…”
Section: B Hydrogen Motion Within the Zinc Vacancymentioning
confidence: 97%
“…18 Contrary to that, isolated hydrogen is preferentially located at the bond-centered lattice site oriented along the c axis (H BC ) and gives rise to a shallow donor level positioned at 53 meV from the bottom of the conduction band. 8 The high mobility of isolated hydrogen at room temperature 19,20 and the Coulomb attraction between H + BC and V 2− Zn results in the formation of V Zn H n complexes. 21 In particular, recent IR absorption studies suggest that V Zn H acts as a deep acceptor in ZnO and gives rise to the 3326 and 3358 cm −1 local vibrational modes (LVMs) assigned to the negative and the neutral charge states of the defect, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the theoretical elucidation of the distinct interstitial hydrogen motions in the ZnO system, it is to be noted that the activation energies for the reorientational and hopping motions are yet to be obtained in a distinct manner [5,[9][10][11][12][13]. NMR is the most powerful tool to directly investigate the structural and dynamical properties of protons in various solids including the ZnO systems [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 97%